Exploratory applications of 2-nitrobenzaldehyde-derived Morita-Baylis-Hillman adducts as synthons in the construction of drug-like scaffolds. Issue 3 (1st February 2019) - Idahosa, Kenudi C.; Davies-Coleman, Michael T.; Kaye, Perry T.
Abstract: Morita- Baylis-Hillman adducts, prepared from 2-nitrobenzaldehyde precursors and either methyl acrylate or methyl vinyl ketone, have been used as critical synthons in the preparation of α-[(alkylamino)methyl]cinnamate esters and their but-3-en-2-one analogs, cinnamate ester-azidothymidine (AZT) conjugates, 2-quinolone and quinoline derivatives. Computer docking studies have been conducted to explore the potential of the cinnamate ester-AZT conjugates as potential dual-action HIV-1 integrase-reverse transcriptase (IN-RT) inhibitors. The results further demonstrate the applicability of Morita-Baylis-Hillman methodology in the construction of complex drug-like scaffolds. GRAPHICAL ABSTRACT: